Plant quarantine - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Plant quarantine: a primer for development workers by Robert Black and Anne Sweetmore 1995 41 pp price UKL7 50 ISBN 0 85954 397 8